Trace elements in viral hepatitis - Kalkan, A; Bulut, V; Avci, S; Celik, I; Bingol, NK (Urban & Fischer Verlag, 2002)
In this study, serum trace elements, including selenium (Se), zinc (Zn), copper (Cu), were determined by using Atomic Absorption Spectrophotometer (SpectrAA 250 Plus Zeeman, Varian, Australia) in sera of patients with viral hepatitis (A, B, C, D, E) cases (n = 102), and statistically compared with the controls (n = 52). In viral hepatitis, Cu levels were found as 3.23 +/- 1.02 mg/L, and this value was significantly higher than the control group (1.13 +/- 0.21) (p < 0.01). Both, Se and Zn Levels found to be significantly Low in viral hepatitis cases (p < 0.01). While Se level was 81.4 +/- 26.01 mug/L in viral hepatitis (n = 101), it was found to be 166.15 +/- 4.58 mug/L in healthy individuals. Meanwhile, Zn Levels were 0.230 +/- 0.081 mg/L and 0.748 +/- 0.392 mg/L in hepatitis cases (n = 101) and the control group, respectively. There was no difference amongst viral hepatitis groups classified in regard with agents and clinical manifestation, such as A, acute hepatitis B, chronic hepatitis B, C, D and E. Previously, it was indicated that absorption disorders in gastrointestinal system, especially in chronic cases, were not main causes of decrease of trace elements by iron and several other parameters in sera of the cases. Therefore, we suggest that decrease in Zn and Se levels and elevation in Cu Levels are probably resulted from defence strategies of organism and induced by the hormone-Like substances.
Keywords: viral hepatitis; selenium; zinc; copper